Examining the relationship between vegetable intake of mothers and that of their children: a cross-sectional study of 10- to 12-year-old schoolchildren in Japan. Issue 17 (21st September 2015) - Tada, Yuki; Tomata, Yasutake; Sunami, Ayaka; Yokoyama, Yuri; Hida, Azumi; Furusho, Tadasu; Kawano, Yukari
Abstract: Objective: The present study aimed to investigate the correlation between mothers' and children's vegetable intake and whether children are conscious about their vegetable intake. Design: Cross-sectional study. Self-administered questionnaires for mothers and children, consisting of items regarding diet history, were distributed to children via homeroom teachers. We created dummy exposure variables for each quartile of mothers' vegetable intake. Multiple regression analysis was performed with children's vegetable intake as the outcome variable. Setting: Two public elementary schools in a residential district of Tokyo, Japan. Subjects: Study participants were upper-grade children (aged 10–12 years) and their mothers (332 pairs of mothers and children). Results: The mean vegetable intake in mothers and children was 310 (sd 145) g/d and 276 (sd 105) g/d, respectively. A positive linear relationship was found between mothers' and children's vegetable intake even after adjustment for considerable covariates ( P <0·001). When stratified by children's consciousness, the positive linear relationship was more pronounced in children who were conscious of eating all their vegetables ( P <0·001 for interaction with children's consciousness). Conclusions: Mothers' vegetable intake was significantly correlated with children's vegetable intake. However, this correlation was stronger in children who were conscious of eating all their vegetables. Our findings suggest that enhancing mother's vegetable intake and health consciousness of children are indispensable prerequisites for increasing vegetable intake among children.